FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2010-2013 - Septian Indra Cahyo, 11.05.52.0014; Setyowati, Widhy (Students Journal of Accounting and Banking, 2015)
The study is done to analyze the influence of the size of the company (size), profitability, risk business, and the growth of assets against capital structure. The object of this study is manufacturing companies who listed on the indonesia stock exchange (BEI) years 2010-2013. The kind of data that is used in this research is of secondary data this data obtained from icmd (the indonesian capital markets directory) 2010-2013. This research do with the methods of sampling purposive to obtain samples in accordance with the criteria have been determined. The total sample gained as much as 61 manufacturing companies with a period of research 2010-2013. Data analysis used is regression analysis test double. Research results show that the partial evaluation company size, risk business, and the growth of influential positive assets significantly to capital structure, while profitability have a negative influence significantly to capital structure. Keywords: Capital Structure, Size of The Company, Profitability, Business Risk, The Growth of Assets